Experimental investigation on a Trailing Edge Morphing Airfoil (TEMA) with zigzag rib structure at low speed - Kodigaddi, Siddalingappa Parameshappa; Venkataramana, Srikanth Holalu; Natesan, Kapilan; Mazlan, Norkhairunnisa (Universiti Putra Malaysia Press, 2025)
Camber-morphing wing technology enables adaptive adjustments to wing curvature by optimizing aerodynamic performance and efficiency for varying flight conditions. This study emphasizes the novel Trailing Edge Morphing Airfoil (TEMA) design and analysis, showcasing its noteworthy aerodynamic characteristics. The design uses the parabolic morphing method to obtain TEMA profiles for deflection angles. The different shapes of the TEMA and base airfoil were analyzed using the XFOIL solver with a linear-vorticity stream function formulation. TEMA with a flexible zigzag section was developed using a 3D printing technique with TPU material. The rectangular wing model was developed using TEMA and tested in a low-speed subsonic wind tunnel with Reynolds numbers of 1.19 ×105, 2.54 × 105 and 3.18 x 105 for different angles of attack. The test cases had a combination of different Reynolds numbers, deflection angles, and angles of attack. The aerodynamic characteristics were calculated by measuring the pressure coefficient around the TEMA using an advanced pressure scanner. The results show that TEMA with a moderate deflection angle has the potential to improve the lift-to-drag ratios by around 30%. It was concluded that TEMA with +5° and +10° deflection angles demonstrated superior aerodynamic efficiency at the Reynolds numbers mentioned compared to the conventional NACA 2412 airfoil.